INFLUENCE OF MOTOR CAPABILITIES ON EFFICACY IN PERFORMING WEDGE TURNING IN ALPINE SKIING - Rašid Hadžić; Dobrislav Vujović; Aldijana Muratović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Goal of this research is to fortify a degree of influence of motor capabilities on efficacy in performing wedge turning in alpine skiing. Research has been conducted on sample of 30 students, average age 22 years, gender-male, 9 motor tests. From derived results come that motor capabilities in showing space have significant influence on successfulness in performing elements of alpine skiing.